2016
DOI: 10.1590/1809-2950/14956323012016
|View full text |Cite
|
Sign up to set email alerts
|

Satisfação de pacientes que recebem cuidados fisioterapêuticos para condições musculoesqueléticas: um estudo transversal

Abstract: las características demográficas y clínicas de los participantes y la Escala de Percepción de Efecto Global (GPE). El MRPS fue descrito mediante la media y desviación estándar. Se calculó los coeficientes de correlación de Pearson para investigar la asociación entre la GPE y la puntuación total del MRPS. Modelos de regresión linear fueron utilizados para analizar las características de los pacientes que podrían predecir la satisfacción total. Se observó alta satisfacción con los cuidados fisioterapéuticos, sie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
3
7
0
2
Order By: Relevance
“…Whereas the men seem to have a lower proportion of health care, since many of times only seek medical care when they perceive signs of illness. However, this study shows that this dispute may be changing, since it was found a gender homogeneity among users, corroborating with the study by Dr. Viana et al 12 and Hush et al 22 56% female, Oliveira et al 18 46% female, Medeiros et al 21 54.6% female gender, indexes close to the 50%, so it is possible to highlight the change in demand for good health.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas the men seem to have a lower proportion of health care, since many of times only seek medical care when they perceive signs of illness. However, this study shows that this dispute may be changing, since it was found a gender homogeneity among users, corroborating with the study by Dr. Viana et al 12 and Hush et al 22 56% female, Oliveira et al 18 46% female, Medeiros et al 21 54.6% female gender, indexes close to the 50%, so it is possible to highlight the change in demand for good health.…”
Section: Resultssupporting
confidence: 90%
“…According to the total average score of 4.34 (SD=0.16) obtained in the questionnaire, we concluded that there is a high level of satisfaction in the study, this average resembles the research by Medeiros et al 21 who had an average of 4.5 (SD=0.4).…”
Section: Resultssupporting
confidence: 85%
“…Thus, we can say that the degree of satisfaction found in this study was high, with an average of 4.75 for the rheumatology sector and 4.52 for the pediatrics sector. Studies conducted in Belo Horizonte, São Paulo and Maceió in Brazil, as well as in India and Australia, show similar results (8,12,(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 59%
“…Medeiros et al [38] analyzed patient satisfaction with treatment for musculoskeletal conditions and found a negative and statistically significant correlation between clinical improvement and patient satisfaction, whereby satisfaction with the treatment seems to be independent of their satisfaction with the clinical outcomes obtained.…”
Section: Discussionmentioning
confidence: 99%